2021
DOI: 10.1172/jci.insight.146827
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to androgen receptor signaling inhibition does not necessitate development of neuroendocrine prostate cancer

Abstract: Resistance to AR signaling inhibitors (ARSis) in a subset of metastatic castration-resistant prostate cancers (mCRPCs) occurs with the emergence of AR – neuroendocrine prostate cancer (NEPC) coupled with mutations/deletions in PTEN , TP53 , and RB1 and the overexpression of DNMTs, EZH2, and/or SOX2. To resolve whether the lack of AR is the driving factor for the emergence of the NE phenotype, molecular, cell, and tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 65 publications
0
34
0
2
Order By: Relevance
“…There are at least five different CRPC tumours reported in patients that can be classified based on AR signature and NE biomarkers: 1) AR-high tumours (ARPC) containing cancer cells expressing uniform AR and AR target genes and no NE markers; 2) AR-low tumours (ARLPC) contains cells with weak or heterogenous AR and PSA expression with no NE markers; 3) amphicrine PCa (AMPC) containing cells co-expressing AR, PSA, and NE markers; 4) small cell neuroendocrine PCa (SCNPC) containing cells with classic small cell carcinoma histology and NE marker positive and no AR and PSA expression; and 5) DNPC containing cells with neither NE marker and AR expression (8,9). These observations are recapitulated in patient-derived xenografts (8,9,(31)(32)(33)(34). Since treatment naïve PCa is predominantly AR and PSA positive tumours, the presentation of ARLPC, SCNPC, and DNPC at the late stage of tumour progression suggests that AR bypass mechanisms are adopted by these tumours.…”
Section: Heterogeneity Of Castrate-resistant Prostate Cancermentioning
confidence: 86%
“…There are at least five different CRPC tumours reported in patients that can be classified based on AR signature and NE biomarkers: 1) AR-high tumours (ARPC) containing cancer cells expressing uniform AR and AR target genes and no NE markers; 2) AR-low tumours (ARLPC) contains cells with weak or heterogenous AR and PSA expression with no NE markers; 3) amphicrine PCa (AMPC) containing cells co-expressing AR, PSA, and NE markers; 4) small cell neuroendocrine PCa (SCNPC) containing cells with classic small cell carcinoma histology and NE marker positive and no AR and PSA expression; and 5) DNPC containing cells with neither NE marker and AR expression (8,9). These observations are recapitulated in patient-derived xenografts (8,9,(31)(32)(33)(34). Since treatment naïve PCa is predominantly AR and PSA positive tumours, the presentation of ARLPC, SCNPC, and DNPC at the late stage of tumour progression suggests that AR bypass mechanisms are adopted by these tumours.…”
Section: Heterogeneity Of Castrate-resistant Prostate Cancermentioning
confidence: 86%
“…PCSK1, encoding prohormone convertase 1, belongs to the proprotein convertase family, and its overexpression has been revealed in various subtypes of neuroendocrine tumors [31][32][33]. Previous studies have shown that treatment-related NEPC also exhibits a high expression of PCSK1, and the pattern of promoter methylation was observed to be different among distinct phenotypes of PCa [34,35]. On the other hand, the role of ASXL3 and TRIM9 in the diagnosis of NEPC has not been previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of AR+, amphicrine, double negative, and NEPC PDXs, Brennen, et al. determined that loss of AR expression was correlated with AR promoter hypermethylation specifically in NEPC models ( 81 ). Beltran, et al.…”
Section: The Role Of Epigenetic Change In Nepc Lineage Plasticitymentioning
confidence: 99%